ZnO-modified amino-modified porous carbon material as well as preparation method and application thereof
Through the ZnO-modified amino-modified porous carbon material, the activation effect of porous activated carbon and ZnO modification is solved, and the existing adsorbent CO2 adsorption effect is achieved with high efficiency and strong selectivity.
Patent Information
- Application Number
- CN202411905048.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing adsorbents for CO2 removal have poor adsorption effect and need to be further improved.
The porous carbon material modified by ZnO is prepared by the steps of preparation, loading, modification and drying of modified solutions. The pore structure of porous activated carbon and the activation effect of ZnO modification are used to achieve efficient adsorption of CO2.
The adsorption effect of CO2 is significantly improved, making the force between the adsorbed material and CO2 stronger, not easy to detach, and has high selectivity and sustainability, and is basically not disturbed by other gases.
Smart Images

Figure BDA0005204189100000251 
Figure BDA0005204189100000261
Abstract
Description
Technical Field
[0001] The invention relates to the field of CO2 adsorbents, and in particular to a ZnO-modified amino-modified porous carbon material and a preparation method and application thereof. Background Art
[0002] Excessive CO2 emissions are the main inducing factor of global environmental changes such as global warming, extreme weather and desertification. At the same time, CO2 is also a product of human metabolism. When the CO2 concentration accumulates to a certain level, it will cause dizziness, nausea and vomiting. When the concentration reaches 5%, human breathing can only be maintained for 30 minutes. When it reaches more than 10%, it will cause people to lose consciousness or even die. Therefore, CO2 must be continuously removed to control the indoor CO2 concentration. In addition, in some chemical processes (such as natural gas purification, sterile wards, fermentation plants, etc.), the concentration of CO2 in the raw gas is strictly controlled. Therefore, it is very important to develop CO2 removal and separation technology for pure CO2.
[0003] At present, the main methods for removing low-concentration CO2 indoors include physical adsorption, membrane separation, metal compound absorption, alcohol amine absorption, etc. These methods have their own advantages, but most of them have the disadvantage of poor adsorption effect. Especially in the small closed / semi-closed space and complex air composition, it is of great significance to study CO2 removal technology with high efficiency, good adsorption effect and convenient operation. Summary of the invention
[0004] Therefore, the main problem to be solved by the present invention is that the adsorbents currently disclosed for CO2 removal have poor adsorption effects and need to be further improved; thus, a ZnO-modified amino-modified porous carbon material and a preparation method and application thereof are provided to solve the above problems.
[0005] A method for preparing a ZnO-modified amino-modified porous carbon material, comprising:
[0006] Preparation of modified solution: dissolving ammonium salt and zinc oxide precursor salt in a solvent to obtain a modified solution, wherein the mass ratio of ammonium salt to zinc oxide precursor salt is (1-10):1;
[0007] Loading: adding porous activated carbon to the modified solution, the mass ratio of porous activated carbon to zinc oxide precursor salt is (1-10):1;
[0008] Modification: add ammonia water to adjust the pH to 8-11, modify under stirring, and evaporate the solvent;
[0009] Drying: Drying to obtain the finished product.
[0010] The drying temperature is 150-200°C;
[0011] And / or, the drying time is 6 to 8 hours;
[0012] And / or, the drying temperature is 100°C to 200°C;
[0013] And / or, the modification time under stirring is 1 to 5 hours.
[0014] The mass ratio of the ammonium salt to the zinc oxide precursor salt is (4-6):1.
[0015] The mass ratio of the porous activated carbon to the zinc oxide precursor salt is (5-10):1.
[0016] The porous activated carbon includes one or more of coconut shell activated carbon, coal-based activated carbon and wood particle activated carbon.
[0017] The ammonium salt includes at least one of ammonium carbonate, ammonium nitrate and ammonium chloride;
[0018] The zinc oxide precursor salt includes at least one of zinc sulfate, zinc nitrate and zinc chloride.
[0019] The solvent is ethanol.
[0020] A ZnO-modified amino-modified porous carbon material is prepared by the above-mentioned preparation method.
[0021] The above-mentioned ZnO-modified amino-modified porous carbon material is used for CO2 adsorption.
[0022] The technical solution of the present invention has the following advantages:
[0023] 1. The present invention provides a method for preparing a ZnO-modified amino-modified porous carbon material, which uses low-cost, commercial porous activated carbon as a carrier, adopts a specific content of raw materials and a specific pH, stirring time, and drying temperature to perform ZnO modification and amino modification, and obtains a ZnO-modified amino-modified porous carbon material with uniform distribution of active components, which can effectively enhance the CO2 surface activation effect, make the interaction between the adsorbent material and CO2 stronger, and not easy to separate, thereby improving the CO2 adsorption effect;
[0024] Specifically, by utilizing the well-developed pore structure and high specific surface area of porous activated carbon to increase the contact area with CO2, CO2 can be effectively adsorbed onto the surface of the porous activated carbon; at the same time, based on ZnO modification, the activation effect of the porous activated carbon surface can be enhanced, and the carbon-oxygen bonds of CO2 can be activated, thereby achieving the effect of enhancing the adsorption and decomposition of CO2; and, the synergistic combination of ZnO modification and amino modification can continuously and highly selectively adsorb CO2 through chemical reactions, and the CO2 adsorption is basically not interfered by other gases, and has a better adsorption effect.
[0025] 2. The preparation method provided by the present invention is simple, has low production cost, is easy to implement, and has good economic benefits and social value. DETAILED DESCRIPTION
[0026] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0027] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0028] Example 1
[0029] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0030] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc sulfate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0031] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0032] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 h, and evaporate the solvent at 80 °C for 1 h;
[0033] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0034] The detection method of CO2 adsorption capacity is as follows:
[0035] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0036] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0037] 3. Adsorption experiment: Place the weighed sample into the sample tube, and then place the sample tube in the heating device of the instrument for pretreatment to further remove impurities and adsorbates on the surface; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C) to ensure that the adsorption process of CO2 on the sample surface is in a low temperature state, which is conducive to improving the measurement accuracy of the adsorption amount; Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0038] Example 2
[0039] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0040] Preparation of modified solution: Dissolve 2.35 g of ammonium nitrate and 1 g of zinc sulfate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0041] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0042] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 h, and evaporate the solvent at 80 °C for 1 h;
[0043] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0044] The detection method of CO2 adsorption capacity is as follows:
[0045] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0046] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0047] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0048] Example 3
[0049] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0050] Preparation of modified solution: Dissolve 1.33 g of ammonium chloride and 1 g of zinc sulfate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0051] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0052] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 h, and evaporate the solvent at 80 °C for 1 h;
[0053] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0054] The detection method of CO2 adsorption capacity is as follows:
[0055] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0056] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0057] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0058] Example 4
[0059] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0060] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc chloride in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0061] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0062] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 h, and evaporate the solvent at 80 °C for 1 h;
[0063] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0064] The detection method of CO2 adsorption capacity is as follows:
[0065] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0066] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0067] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0068] Example 5
[0069] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0070] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0071] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0072] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 h, and evaporate the solvent at 80 °C for 1 h;
[0073] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0074] The detection method of CO2 adsorption capacity is as follows:
[0075] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0076] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0077] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0078] Example 6
[0079] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0080] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0081] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0082] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0083] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0084] The detection method of CO2 adsorption capacity is as follows:
[0085] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0086] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0087] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0088] Example 7
[0089] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0090] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0091] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0092] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0093] Drying: Dry at 200℃ for 2h to obtain the finished product.
[0094] The detection method of CO2 adsorption capacity is as follows:
[0095] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0096] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0097] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0098] Example 8
[0099] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0100] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0101] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0102] Modification: Add ammonia water dropwise under stirring to adjust the pH to 11, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0103] Drying: Dry at 200℃ for 2h to obtain the finished product.
[0104] The detection method of CO2 adsorption capacity is as follows:
[0105] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0106] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0107] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0108] Example 9
[0109] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0110] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0111] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0112] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0113] Drying: Dry at 200℃ for 6h to obtain the finished product.
[0114] The detection method of CO2 adsorption capacity is as follows:
[0115] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0116] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0117] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0118] Example 10
[0119] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0120] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0121] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0122] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0123] Drying: Dry at 150℃ for 2h to obtain the finished product.
[0124] The detection method of CO2 adsorption capacity is as follows:
[0125] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0126] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0127] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0128] Embodiment 11
[0129] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0130] Preparation of modified solution: Dissolve 10 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0131] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0132] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0133] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0134] The detection method of CO2 adsorption capacity is as follows:
[0135] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0136] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0137] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0138] Example 12
[0139] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0140] Preparation of modified solution: Dissolve 8 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0141] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0142] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0143] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0144] The detection method of CO2 adsorption capacity is as follows:
[0145] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0146] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0147] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0148] Embodiment 13
[0149] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0150] Preparation of modified solution: Dissolve 6 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0151] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0152] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0153] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0154] The detection method of CO2 adsorption capacity is as follows:
[0155] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0156] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0157] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0158] Embodiment 14
[0159] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0160] Preparation of modified solution: Dissolve 4 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0161] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0162] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0163] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0164] The detection method of CO2 adsorption capacity is as follows:
[0165] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0166] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0167] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0168] Embodiment 15
[0169] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0170] Preparation of modified solution: Dissolve 4 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0171] Loading: 8 g coconut shell activated carbon was added to the modified solution;
[0172] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0173] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0174] The detection method of CO2 adsorption capacity is as follows:
[0175] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0176] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0177] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0178] Example 16
[0179] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0180] Preparation of modified solution: Dissolve 4 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0181] Loading: 10 g coconut shell activated carbon was added to the modified solution;
[0182] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0183] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0184] The detection method of CO2 adsorption capacity is as follows:
[0185] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0186] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0187] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0188] Embodiment 17
[0189] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0190] Preparation of modified solution: Dissolve 4 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0191] Loading: 1 g coconut shell activated carbon was added to the modified solution;
[0192] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0193] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0194] The detection method of CO2 adsorption capacity is as follows:
[0195] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0196] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0197] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0198] Embodiment 18
[0199] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0200] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0201] Loading: Add 5 g of wood activated carbon to the modified solution;
[0202] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and stir at 80 °C for 1 h to evaporate the solvent;
[0203] Drying: Dry at 200℃ for 2h to obtain the finished product.
[0204] The detection method of CO2 adsorption capacity is as follows:
[0205] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0206] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0207] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0208] Comparative Example 1
[0209] A method for preparing a porous carbon material, the specific preparation process is as follows:
[0210] Pretreatment: Add 5 g coconut shell activated carbon to 50 mL ethanol;
[0211] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 hour, and evaporate the solvent;
[0212] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0213] The detection method of CO2 adsorption capacity is as follows:
[0214] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0215] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0216] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0217] Comparative Example 2
[0218] A method for preparing a ZnO-modified porous carbon material, the specific preparation process is as follows:
[0219] Preparation of modified solution: Dissolve 1 g zinc sulfate in 50 mL ethanol and stir until fully dissolved to obtain a modified solution;
[0220] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0221] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 hour, and evaporate the solvent;
[0222] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0223] The detection method of CO2 adsorption capacity is as follows:
[0224] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0225] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0226] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0227] Comparative Example 3
[0228] A method for preparing an amino-modified porous carbon material, the specific preparation process is as follows:
[0229] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate in 50 mL of ethanol and stir to fully dissolve to obtain a modified solution;
[0230] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0231] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 hour, and evaporate the solvent;
[0232] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0233] The detection method of CO2 adsorption capacity is as follows:
[0234] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0235] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0236] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0237] Comparative Example 4
[0238] A method for preparing a ZnO-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0239] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of zinc sulfate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0240] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0241] Modification: NaOH solution was added dropwise under stirring to adjust the pH to 8, stirred for 1 h, and the solvent was evaporated by stirring at 80 °C for 1 h;
[0242] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0243] The detection method of CO2 adsorption capacity is as follows:
[0244] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0245] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0246] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0247] Comparative Example 5
[0248] A method for preparing a Mg-modified amino-modified porous carbon material, the specific preparation process is as follows:
[0249] Preparation of modified solution: Dissolve 1.39 g of ammonium carbonate and 1 g of magnesium nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0250] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0251] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 hour, and evaporate the solvent;
[0252] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0253] The detection method of CO2 adsorption capacity is as follows:
[0254] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0255] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0256] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0257] Comparative Example 6
[0258] A method for preparing a Mg-modified porous carbon material, the specific preparation process is as follows:
[0259] Preparation of modified solution: Dissolve 1 g of magnesium nitrate in 50 mL of ethanol and stir until fully dissolved to obtain a modified solution;
[0260] Loading: Add 5 g coconut shell activated carbon to the modified solution;
[0261] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 1 hour, and evaporate the solvent;
[0262] Drying: Dry at 100℃ for 2h to obtain the finished product.
[0263] The detection method of CO2 adsorption capacity is as follows:
[0264] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0265] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0266] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0267] Comparative Example 7
[0268] A method for preparing a porous carbon material, the specific preparation process is as follows:
[0269] Pretreatment: Add 5 g of wood activated carbon to 50 mL of ethanol;
[0270] Modification: Add ammonia water dropwise under stirring to adjust the pH to 8, stir for 5 h, and evaporate the solvent;
[0271] Drying: Dry at 200℃ for 2h to obtain the finished product.
[0272] The detection method of CO2 adsorption capacity is as follows:
[0273] 1. Sample processing: Weigh the sample of the material to be tested (the finished product of this embodiment), accurately weigh the dried sample, and weigh 100 mg of the sample to an accuracy of 0.1 mg;
[0274] 2. Instrument preparation: Use a physical adsorption instrument (BET analyzer) and calibrate it according to the instrument manual to ensure the accuracy and reliability of the instrument;
[0275] 3. Adsorption experiment: Place the weighed sample into a sample tube, and then place the sample tube in the heating device of the instrument for pretreatment; Cooling: Cool the pretreated sample to liquid nitrogen temperature (about -196°C); Adsorption measurement: Expose the sample to CO2 gas at 1 atmosphere and measure the CO2 adsorption amount (mg / g) at this pressure.
[0276] The CO2 adsorption results of the above-mentioned embodiments and comparative examples are shown in Tables 1 to 4 below.
[0277] Table 1
[0278] sample <![CDATA[CO2 adsorption capacity (mg / g)]]> sample <![CDATA[CO2 adsorption capacity (mg / g)]]> Example 1 340 Example 10 348 Example 2 333 Embodiment 11 320 Example 3 332 Example 12 322 Example 4 342 Embodiment 13 363 Example 5 345 Embodiment 14 364 Example 6 360 Embodiment 15 365 Example 7 365 Example 16 363 Example 8 355 Embodiment 17 353 Example 9 358 Embodiment 18 288
[0279] Table 2
[0280] sample <![CDATA[CO2 adsorption capacity (mg / g)]]> Example 1 340 Comparative Example 1 283 Comparative Example 2 300 Comparative Example 3 315 Comparative Example 4 290
[0281] Table 3
[0282] sample <![CDATA[CO2 adsorption capacity (mg / g)]]> Comparative Example 5 291 Comparative Example 1 283 Comparative Example 3 315 Comparative Example 6 284
[0283] Table 4
[0284]
[0285]
[0286] As shown in Tables 1-2 and 4, the present invention can significantly improve the adsorption effect by adjusting the pH value through ZnO modification and amino modification in coordination with ammonia water, compared with single ZnO modification and single amino modification. However, as shown in Table 3, there is no synergistic effect between other metal modifications and amino modification.
[0287] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A method for preparing a ZnO-modified amino-modified porous carbon material, characterized in that: include: Preparation of modified solution: dissolving ammonium salt and zinc oxide precursor salt in a solvent to obtain a modified solution, wherein the mass ratio of ammonium salt to zinc oxide precursor salt is (1-10):1; Loading: adding porous activated carbon to the modified solution, the mass ratio of porous activated carbon to zinc oxide precursor salt is (1-10):1; Modification: add ammonia water to adjust the pH to 8-11, modify under stirring, and evaporate the solvent; Drying: Drying to obtain the finished product.
2. The preparation method according to claim 1, characterized in that: The drying temperature is 150-200°C; And / or, the drying time is 6 to 8 hours; And / or, the drying temperature is 100°C to 200°C; And / or, the modification time under stirring is 1 to 5 hours.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the ammonium salt to the zinc oxide precursor salt is (4-6):
1.
4. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the porous activated carbon to the zinc oxide precursor salt is (5-10):
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The porous activated carbon includes one or more of coconut shell activated carbon, coal-based activated carbon and wood particle activated carbon.
6. The preparation method according to any one of claims 1 to 4, characterized in that: The ammonium salt includes at least one of ammonium carbonate, ammonium nitrate and ammonium chloride.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The zinc oxide precursor salt includes at least one of zinc sulfate, zinc nitrate and zinc chloride.
8. The preparation method according to any one of claims 1 to 4, characterized in that: The solvent is ethanol.
9. A ZnO-modified amino-modified porous carbon material, characterized in that: The preparation method is described in any one of claims 1 to 8.
10. Use of the ZnO-modified amino-modified porous carbon material according to claim 9 in CO2 adsorption.
Citation Information
Patent Citations
Porous carbon material and preparation method thereof
CN113426410A
Method of forming syngas for producing liquid hydrocarbons
CN118742509A
Moisture conditioning coating
JP2008019295A
Carbon dioxide adsorbent and carbon dioxide recovery apparatus using the same
JP2014083488A